PENGARUH METODE LATIHAN DAN POWER OTOT TUNGKAI TERHADAP KEMAMPUAN JUMP SHOT BOLABASKET - Wanena, Tery; Muhammad, Junalia (Sains Olahraga : Jurnal Ilmiah Ilmu Keolahragaan, 2020)
This research attemps to find out a) impact difference between distributed training and drill training to basketball jump shoot result, b) result difference of basket ball jump shoot between basketball UKM FIK Uncen students with low and high leg muscle power, and c) interaction impact between traning method and leg muscle power to basketball jump shot result of basketball UKM FKM FIK Uncen students. The training method developed to increase tecnique skill with practice distributed method (distributed training) and massed practice (drill practice). The teories ini this research used training method, jump shoot, and leg muscle power. The research method used experimental metod with 2 x 2 factorial sample. The factorial experimental method is a experiment with two or more free variables (at least one manipulated). The subjects used 20 persons of FIK Uncen Basketball students. The result shows there are impact difference between distributed training method and drill traning method to basketball jump shot power of UKM FIK Uncen basketball students (Fo = 7,674 > Ft = 4,11). There is impact difference between low and high leg muscle power to basketball jump shot power of UKM FIK Uncen students with (Fo = 4,642 > Ft = 4,11). And also, there is interaction between training method with leg muscle power to basketball jump shoot of basketball UKM FIK Uncen students (Fo = 12,895 >Ft = 4,11). Because of that, drill training method more effective applied for high leg muscle power player, whereas distributed training method more effective applied to low leg muscle power player. Key words : Training method, power, jump shoot